ANALISIS BUDAYA ORGANISASI DIKANTOR BUPATI TOLITOLI - Lestari, Ayu (Katalogis, 2017)
This study aimed to determine the organizational culture at TolitoliRegent Office, organizational culture at Tolitoli Regent Office still less than optimal, marked by its work-family culturethat was still very attached.This study used qualitative research method, where the informants in this study consisted of Tolitoli Secretary as the key informant and the employees of Tolitoli Regent Office. Data were collected using observations, interviews, and documentations. The results show that organizational culture at Tolitoli Regent Office still less than optimal.Based on organizational culture indicators of Stephen P Robbins (2014:487), employeeselection should be based on human resources and skills (ability):Staffing in Tolitoli Regent Office was still based on its proximity to the leader. The top management wasseen from behavior and norms: Briefing from the leader to the employees of Tolitoli Regent Officewas always carried out, but in terms of implementation,the discipline ofthe employees was still less than optimal. Socialization in terms of environmental andwork values:Cooperation amongemployees hadrun quite optimally, every employee was able to cooperate well enough to achieve the goals of the organization among divisions. Every employee should be able to understand the duties and functions of each if you did not understand how he works well.Of course, it is the most fundamental to every employee. However, an organization should do recruitment and selection, an employee must comply with the applicable rules and also look at his ability.